Driving forces of the Swiss output gap - Stefan Leist (University of Bern, Department of Economics, 2011)
Contrary to standard agnostic statistical approaches an output gap estimate based on a New Keynesian Small Open Economy model provides the possibility to analyze the driving forces of the variation in GDP caused by nominal rigidities. This paper makes use of this and provides an estimate of a model based output gap that corresponds well with conventional measures. The results confirm conventional wisdom that most of the variation is due to foreign shocks. But the risk premium shock in the uncovered interest rate parity equation also plays an important role. It has a procyclical effect on the output gap except for the last recession.
Keywords: C11; C51; E32; F41; 330; DSGE models; output gap; natural level of output; small open economy; business cycle; recessions; Sozialprodukt; Gesamtwirtschaftliche Produktion; Dynamisches Gleichgewicht; Neukeynesianische Makroökonomik; Offene Volkswirtschaft; Schweiz